2014
DOI: 10.1073/pnas.1414358111
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme Ubc13 controls breast cancer metastasis through a TAK1-p38 MAP kinase cascade

Abstract: Metastatic spread is the leading cause of cancer mortality. Breast cancer (BCa) metastatic recurrence can happen years after removal of the primary tumor. Here we show that Ubc13, an E2 enzyme that catalyzes K63-linked protein polyubiquitination, is largely dispensable for primary mammary tumor growth but is required for metastatic spread and lung colonization by BCa cells. Loss of Ubc13 inhibited BCa growth and survival only at metastatic sites. Ubc13 was dispensable for transforming growth factor β (TGFβ)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 61 publications
(72 reference statements)
7
98
1
Order By: Relevance
“…41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation. This in turn could suggest that different cyclophilins and in particular CypA can function as a molecular switch to modulate p38MAPK signalling to adjust to environmental changes, thus modulating cancer cell survival.…”
Section: Discussionsupporting
confidence: 64%
“…41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation. This in turn could suggest that different cyclophilins and in particular CypA can function as a molecular switch to modulate p38MAPK signalling to adjust to environmental changes, thus modulating cancer cell survival.…”
Section: Discussionsupporting
confidence: 64%
“…A recent report has implicated p38a, downstream of the ubiquitin-conjugating enzyme Ubc13 and the kinase TAK1, in the metastatic dissemination of breast cancer cells to the lung in mouse models. Moreover, p38a and Ubc13 expression correlates with worse overall survival in human patients with breast cancer (21).…”
Section: Metastasismentioning
confidence: 98%
“…Thus, p38a inhibitors may suffice to impair the growth of tumors where this pathway is required for cancer cell proliferation or survival, but these inhibitors could potentially stimulate tumorigenesis in other tissues. There is also evidence for dual roles of p38a in metastasis, as downregulation of p38a signaling facilitates the metastatic spread of colon cancer cells from liver to lung (18), whereas a p38a pharmacologic inhibitor attenuates breast cancer metastasis (21). The development of new therapeutic strategies clearly requires a better understanding of the specific targets involved in the different functions of p38a and how they contribute to specific tumoral processes In addition, recent data strongly implicate p38a signaling in the resistance to chemotherapeutic treatments.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Crucially, MEKK1 and TAK1 are also required for the metastasis of cancer cells (Cuevas et al, 2006;Safina et al, 2008). A recently published paper showed that UBC13 controls breast cancer metastasis via TAK1-p38 MAP kinase cascades (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%